KAJIAN SIFAT FISIK TANAH UNTUK TANAMAN PISANG ABAKA (Musa textilis NEE) DI PERKEBUNAN PT.VIOLA FIBER INTERNASIONAL KABUPATEN MINAHASA TENGGARA - Ronald Batubuaya; Yani E. B. Kamagi; Berry R. V. Joseph. (COCOS, 2018)
ABSTRACT  This research aimed to find out some physical properties of the soil for the developing the abaca banana at Silian Village, Silian Raya Sub district, Southeast Minahasa Regency, whether conditions at that location was suitable for the development of the banana plant abaca (Musa textilis NEE), or not.  This research was carried out on site estate of PT. Viola International Fiber in Silian Village.  Taking the soil samples at a depth of 0-20 cm and 20-40 cm in as many as six points.  Soil analysis was done in the Laboratory of Physics and Soil Conservation Soil Department, Faculty of Agriculture, University of Sam Ratulangi Manado.  The research was conducted with Descriptive Survey Method and the data ware collected in the form of a table, then drawn up and analyzed were descriptive.  The observed parameters were: soil texture, soil permeability, soil bulk density, moisture content of the soil, rainfall data, and elevation. The results of this study showed that, data and information on the physical properties of soils and the condition of the site showed that the land was suitable for crop growth of abacá.  Key words: physical properties of soils, Banana and Abaca (Musa textilis NEE)